1991
DOI: 10.1152/jappl.1991.71.2.438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triiodothyronine-induced thyrotoxicosis on airway hyperresponsiveness

Abstract: To determine whether thyrotoxicosis has an effect on the asthmatic state in subjects with mild asthma, airway responsiveness, lung function, and exercise capacity were measured in a randomized double-blind placebo-controlled trial before and after liothyronine (triiodothyronine, T3)-induced thyrotoxicosis. Baseline evaluation of 15 subjects with mild asthma included clinical evaluation, thyroid and routine pulmonary function tests, airway responsiveness assessment by methacholine inhalation challenge, and a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Persistent airway hyperresponsiveness is present in the majority of patients with chronic asthma and is considered to reflect airway remodeling (9). Studies on the effects of thyroid hormones on airway hyperresponsiveness in vivo have shown that mild thyreotoxicosis induced by 4 wk of treatment with T 3 does not affect lung function, exercise capacity, or airway hyperresponsiveness in asthmatic patients (20). Similarly, T 3 -induced hyperthyroidism does not affect airway reactivity or lung function in healthy volunteers (21).…”
Section: L304mentioning
confidence: 99%
“…Persistent airway hyperresponsiveness is present in the majority of patients with chronic asthma and is considered to reflect airway remodeling (9). Studies on the effects of thyroid hormones on airway hyperresponsiveness in vivo have shown that mild thyreotoxicosis induced by 4 wk of treatment with T 3 does not affect lung function, exercise capacity, or airway hyperresponsiveness in asthmatic patients (20). Similarly, T 3 -induced hyperthyroidism does not affect airway reactivity or lung function in healthy volunteers (21).…”
Section: L304mentioning
confidence: 99%
“…Susceptibility to infections does not appear to increase with altered thyroid function, but the high incidence of hypothyroidism in septic patients may contribute to cardiovascular instability [67], however this susceptibility has not been related, to date, to altered leukocyte function. Hyperthyroidism may exacerbate the severity to and susceptibility to asthma [66], although this view is not universally accepted [68]. Hypothyroidism may ameliorate coexistent allergic reactions since thyroidectomized rats experience a less severe pulmonary inflammation upon antigen challenge, possibly due to lower levels of IgE antibody [69], and/or reduced production of superoxide production by alveolar macrophages and neutrophils [69,70].…”
Section: Thyroid Hormonesmentioning
confidence: 99%